TRIAGE - Zarifyan, Alla (MD Conference Express, 2015)
The TRIAGE study was conducted to determine whether platelet reactivity testing added to clinical assessment of patients treated with prasugrel vs clopidogrel would better identify patients at high ischemic risk. However, low enrollment resulted in a sample size too small to detect a between-group difference; none was found for any of the prespecified efficacy or safety outcomes.